A Global Phosphorylation Atlas of Proteins Within Pathological Site of Rotator Cuff Tendinopathy - Wang, Yezhou; Zhang, Jiawei; Lin, Yuan; Cheng, Shi; Wang, Duanyang; Rao, Man; Jiang, Yuheng; Huang, Xiang; Chen, Ruijing; Xie, Yong; Yin, Pengbin; Cheng, Biao (Frontiers in Molecular Biosciences, 2022)
Background: Rotator cuff tendinopathy (RCT) is the most common cause of shoulder pain, posing an important clinical problem. However, due to a lack of understanding in the mechanism, no specific agent targeting on any biological pathway exists. Phosphorylation, as an important and well-studied post-translational modifications, is tightly associated with protein activity and supposed to play a part in RCT. Methods:Nine patients diagnosed as RCT were recruited. By using TMT labeling combining with mass spectrometry, phosphorylation sites and proteins were identified. Functional analysis of proteins was determined by gene ontology enrichment. Results:An average of 7741 p-sites and 3026 proteins were identified. Compared to normal counterpart, 1668 p-sites in 706 proteins were identified as upregulated, while 73 p-sites in 57 proteins were downregulated. GO enrichment analyses have shown majority proteins with upregulated p-sites functioned in neutrophil mediated immunity whereas downregulated mainly involved in muscle development. Pathway analysis identified NF-κB related TNF signaling pathway and PKCA related Wnt signaling pathway were associated with RCT. At last, a weighted kinase-site phosphorylation network was built to identify potentially core kinase, from which STLK3 and MST1 were proposed to positively correlated with activation of Wnt pathway.